Policy on Development of Cultural Industries in Vietnam - Nguyễn, Thị Anh Quyên (2023)
From 1986 up to now, after 36 years of the comprehensive renovation of socio-economic institutions in Vietnam, institutional reform in the cultural field with more cautious steps took place later compared to institutional reform in the economic field. However, changes in the legal framework for cultural management have had a significant impact on the operation of cultural industries. From a heavily subsidized social institution, Vietnamese culture transformed into cultural industries, although it was still very fragmented, it brought new vitality to the restoration and development of cultural values through the creation and diffusion of these values in the form of cultural products and services. Vietnam's cultural industriesdevelopment is entering a new phase, with both favorable conditions, difficulties, and challenges. The deepening international integration not only brings great opportunities for the creation of cultural products but also creates great competitive pressureIn that context, the future development of Vietnam's cultural industries is partly influenced by the progress of the Vietnamese government's cultural reform. Cultural industries developing policies in Vietnam are regulations of the State that create a close combination of culture, arts, economy, and technology. From a policy perspective, the author's article uses qualitative research methods, based on inheriting the theory of cultural industries development and Vietnamese practice; from which to propose solutions to complete the development of cultural industries in Vietnam in the coming time.